Making Memories of Stressful Events: A Journey Along Epigenetic, Gene Transcription, and Signaling Pathways - Reul, Johannes M.H.M. (Frontiers in Psychiatry, 2014)
Strong psychologically stressful events are known to have a long-lasting impact on behavior. The consolidation of such, largely adaptive, behavioral responses to stressful events involves changes in gene expression in limbic brain regions such as the hippocampus and amygdala. The underlying molecular mechanisms however were until recently unresolved. More than a decade ago we started to investigate the role of these hormones in signaling and epigenetic mechanisms participating in the effects of stress on gene transcription in hippocampal neurons. We discovered a novel, rapid non-genomic mechanism in which glucocorticoids via glucocorticoid receptors (GRs) facilitate signaling of the ERK MAPK signaling pathway to the downstream nuclear kinases MSK1 and Elk-1 in dentate gyrus (DG) granule neurons. Activation of this signaling pathway results in serine10 (S10) phosphorylation and lysine14 (K14) acetylation at histone H3 (H3S10p-K14ac), leading to the induction of the immediate early genes c-Fos and Egr-1. In addition, we found a role of the DNA methylation status of gene promoters. A series of studies showed that these molecular mechanisms play a critical role in the long-lasting consolidation of behavioral responses in the forced swim test and Morris water maze. Furthermore, an important role of GABA was found in controlling the epigenetic and gene transcriptional responses to psychological stress. Thus, psychologically stressful events evoke a long-term impact on behavior through changes in hippocampal function brought about by distinct glutamatergic and glucocorticoid-driven changes in epigenetic regulation of gene transcription which are modulated by (local) GABAergic interneurons and limbic afferent inputs. These epigenetic processes may play an important role in the etiology of stress-related mental disorders such as major depressive and anxiety disorders like PTSD.